Implementation of information competencies as key employment skills at the Faculty of Humanities and Social Sciences - Špiranec, Sonja (Array, 2014)
In order to improve the quality of their study programs, universities/faculties today are facing increasing demands to include employment skills into their curricula in order to maximize the potential of their students for a successful career. One of the key aspects in developing such skills is increasing students’ employability - a set of skills, understandings and personal attributes that make graduates more likely to gain employment and be successful in their chosen occupations, which benefits themselves, the workforce, the community and the economy. While there is a broad consensus amongst key stakeholders in the process (HEI, employers, students) on the importance of addressing employment skills within higher education, there are still open questions on how this can be achieved. While universities/faculties tend to put more emphasis on developing specific knowledge and skills within their field of education, a number of reports issued by employers urged them to make more explicit efforts to develop the “transferable” or “generic” skills needed in many types of high-level employment. In an ever increasing world of information, as one of the core components of these generic skills is developing information competencies – skill set needed for effective gathering, evaluating and communicating information in all its forms and contexts. This paper aims to explore how these information competencies are implemented at the Faculty of Humanities and Social Sciences, University of Zagreb by conducting research across its study programs on the masters’ level. Following that approach, this research will provide a snapshot of current situation and give recommendations on possible optimizations in including information competences into the curricula at the faculty level.